2009
DOI: 10.1590/s1413-70542009000300033
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survival of tilapia Oreochromis niloticus (Linnaeus, 1758) submitted to different temperatures during the process of sex reversal

Abstract: The objective of this research was to evaluate the sex reversal technique using 17 --methyltestosterone (MT) hormone, submitted to temperature modification of fry Nilo tilapia storage, aiming to get the data of sex reversal combined with growth performance and fry survival. The experiment was performed at UFLA Fish Culture Station, using tilapia fry (0,008 ± 0.002 g e 0,9 ± 0.1 cm) obeying a totally randomized experimental delineation in a factorial scheme 4x4, in 4 temperatures (26º, 28º, 30º, 32ºC) and 4 hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…In the same trend, increasing rearing water temperature to 30 or 35°C without 17α-MT (C30H0 and C35H0) significantly increased mortality rate to 14.00 and 14.33% after one week; 15.33 and 15.00% after two weeks; 15.33 and 15.17% after three weeks and 15.83 and 16.83% after four weeks of treatment. These results are in agreement with those observed by Drummond et al, (2009) who found that, the values of survival (%) of O. niloticus after 28 days of treatment there was significant interaction of temperatore (26, 28, 30 and 30°C) and hormonal doses (0, 20, 40 and 60 mg17α-MTkg diet).…”
Section: Mortality Ratesupporting
confidence: 93%
See 2 more Smart Citations
“…In the same trend, increasing rearing water temperature to 30 or 35°C without 17α-MT (C30H0 and C35H0) significantly increased mortality rate to 14.00 and 14.33% after one week; 15.33 and 15.00% after two weeks; 15.33 and 15.17% after three weeks and 15.83 and 16.83% after four weeks of treatment. These results are in agreement with those observed by Drummond et al, (2009) who found that, the values of survival (%) of O. niloticus after 28 days of treatment there was significant interaction of temperatore (26, 28, 30 and 30°C) and hormonal doses (0, 20, 40 and 60 mg17α-MTkg diet).…”
Section: Mortality Ratesupporting
confidence: 93%
“…The combined effect of rearing water temperature and 17α-MT treatment indicated a significant increase in male ratio compared to the effect of water temperature or 17α-MT alone and these results showed the possibility of reducing hormone treatment period from 4 to 2 weeks by increasing rearing water temperature to 30 or 35°C with obtaining an appropriate male population (93.33 and 96.67%, respectively) and this could be reduce hormone costs and its problems in producing sex reversal of O. niloticus fry. On the other hand, Drummond et al, (2009) found no significant interaction between temperatore (26, 28, 30 and 30°C) and hormonal doses (0, 20, 40 and 60 mg17α-MTkg diet) for sex ratio of O. niloticus fry used for sex reversal.…”
Section: Sex Ratiomentioning
confidence: 63%
See 1 more Smart Citation
“…Tilápia é o nome genérico de um grande número de espécies de peixes da espécie de ciclídeos (DRUMMOND;MURGAS;VICENTINI, 2009). A distribuição original deste grupo foi no centro-sul da África para o norte na Síria (POP-MA; PHELPS, 1998), portanto da família Cichlidae, nativo do continente Africano e da Ásia Menor (GURGEL, 1998).…”
Section: Introductionunclassified
“…The survival rate of O. niloticus was is higher with natural food compared to artificial feed [12]. Remarkable growth and survival performance of tilapia have been observed at around 30ºC [13]. The growth of fish performs better in p H ranging from 5.66-7.66 [14].…”
Section: Introductionmentioning
confidence: 99%